Macular Edema Secondary to Retinal Vein Occlusion in a Real-Life Setting: a Multicenter, Nationwide, 3-Year Follow-Up Study - Costa, JV (2022)
Purpose: To evaluate the presence of macular edema secondary to retinal vein occlusion (RVO)-both central retinal vein occlusion (CRVO) and branch retinal vein occlusion (BRVO)-3 years after diagnosis in patients who underwent intravitreal therapy and to identify potential prognostic factors and biomarkers of persistent macular edema. Methods: National multicenter, observational, exploratory, retrospective cohort study of 104 consecutive patients with macular edema secondary to RVO diagnosed from January 2014 to December 2015 with minimum 3-year follow-up time. Data analyzed included best-corrected visual acuity (BCVA), clinical and demographic data, and spectral domain optical coherence tomography parameters. Results: At final observation, median baseline central retinal thickness significantly improved from baseline 538 to 290 μm (p < 0.001) and complete macular edema resolution was achieved in 51.0% of patients (56.3% and 42.5% in BRVO and CRVO patients, respectively). BCVA also improved (p < 0.01). Logistic regression analysis revealed a relationship between recurrence of macular edema and disorganization of retinal inner layers (DRIL) at baseline (odds ratio = 2.88; p = 0.013). Conclusion: Good long-term anatomical and functional outcomes are achieved with intravitreal treatments in RVO patients. Anatomical success and visual gains seen in the first year were maintained throughout the entire follow-up, though DRIL is a major risk factor for recurrence.